Effects of Knee Flexion Angle and Loading Conditions on the End-to-End Distance of the Posterior Cruciate Ligament: A Comparison of the Roles of the Anterolateral and Posteromedial Bundles. (December 2014) - Wang, Joon Ho; Kato, Yuki; Ingham, Sheila J.M.; Maeyama, Akira; Linde-Rosen, Monica; Smolinski, Patrick; Fu, Freddie H.; Harner, Christopher
Background: It is commonly accepted that the anterolateral (AL) bundle of the posterior cruciate ligament (PCL) is tight in flexion and that the posteromedial (PM) bundle is tight in extension. However, a recent in vivo study showed that both bundles were tight in extension. Purpose: To investigate the effects of knee flexion angle, rotational torque, and anterior/posterior translational force on the end-to-end distance between the femoral and tibial insertion sites of each bundle of the PCL. Study Design: Descriptive laboratory study. Methods: Cadaveric knees (10 specimens) were mounted on a robotic system, and the relative positional data between the femur and tibia were acquired during passive flexion/extension, with an applied 5-N·m rotational torque and an applied 89-N translational force. The bony surface and PCL insertion data were acquired with a 3-dimensional scanner after gross dissection and were superimposed onto the positional data. The end-to-end distance between the 2 PCL insertion sites of the femur and tibia was measured. Results: The end-to-end distance increased from full extension to 90° for both the AL (9.2 ± 1.8 mm; from 30.0 to 39.2 mm) and PM bundles (5.8 ± 2.2 mm; from 32.0 to 37.7 mm). With an internal rotational torque, the end-to-end distance of the PM bundle increased significantly ( P < .05) at 0°, 30°, and 60° of knee flexion. Under a posterior translational force at 90° of knee flexion, the length of both bundles increased to their longest measurements (AM bundle: 40.6 ± 4.2 mm; PM bundle: 38.4 ± 3.8 mm). Conclusion: The end-to-end distance of the AL and PM bundles of the PCL increased in flexion, and this pattern was maintained during tests with posterior translational force. The PM bundle was more affected by the rotational torque than was the AL bundle. Clinical Relevance: Both bundles of the PCL may serve a greater functional role in flexion than in extension. The PM bundle might be more important for the control of rotation than the AL bundle. Posterior translation at 90° of knee flexion could be the most stressful condition for both bundles of the PCL, which may have implications for an injury mechanism.